Investigation of the effects of atmospheric pressure cold and hot plasma on the adhesive bond strength of Al 5049 and CFRP - Yunus Emre Nehri; Ali Oral; Kadir Çavdar (Materials Research Express)
In this study, the effects of atmospheric pressure cold and hot plasma treatment on the adhesive bond strength of 5049 aluminum alloy (5049) and carbon fiber reinforced polymer composite (CFRP) were investigated. For this purpose, plasma treatments were applied to sample surfaces prepared in accordance with the standard dimensions. The experimental design was created with a Central Composite Design using the Response Surface Method (RSM) with 3 different application distances and 3 different numbers of passes as plasma parameters. The contact angles of samples to which atmospheric pressure cold and hot plasma were applied and which were not plasma treated were measured. Depending on the experimental design, the adhesive strengths of the single-lap joint samples were determined by tensile test after the applied plasma treatments. As a result of atmospheric pressure cold plasma application, the average contact angle values decreased by 13.68% on the 5049 surface and 11.86% on the CFRP surface. As a result of hot plasma application, the average contact angle values decreased by 26.04% on the 5049 surface and 30.08% on the CFRP surface. Shear stress results of single-lap joints showed an increase of 5.83% after atmospheric pressure cold plasma and 7.97% after hot plasma.